Substitution reactions between arenethiolate anions and 1,3-dihalo-2,2-dimethylpropanes. Synthetic scope and mechanistic aspects - Barrionuevo, Cecilia Andrea (2011)
The synthetic scope of the reactions between benzenethiolate, 4-methoxybenzenethiolate, 2-naphthalenethiolate, and 2-pyridinethiolate anions with 1,3-dihalo-2,2-dimethylpropane was studied. These reactions render mono and disubstituted products from good to excellent yields. For all the substrates studied the monosubstituted halogenated product is the intermediate or the main product depending on the nature of the second leaving group. Aryl cyclopropyl sulfides were found as side products and their yields strongly depend on the base concentration (tert-BuOK). Finally, using neopentyl iodide as a model, the mechanism of these reactions was evaluated based on non-kinetic evidence, demonstrating that the reactions switch from SRN1 to polar SN2 according to the solvent employed. © ARKAT-USA, Inc.